(untitled) (Економіка і регіон/ Economics and region, 2021)
In the article features and role of marketing communications, particularly in the aspect of influence and interaction between categories “brand”, clients-consumers of brand’s products are considered. The specifics of companies’ activities in the field of communications are studied. There are considered tasks and elements of formation of marketing communications policy in this paper. The characteristic of the basic means of a complex of advancement, as a program of enterprises’ marketing communication are given. It is substantiated that the client’s avatar is the basis for the formation of marketing communications. There are made appropriate conclusions, regarding the further improvement of marketing communications at the enterprise.